2017
DOI: 10.18006/2017.5(1).070.076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antioxidant properties of the most common coffee brews available in the local markets of the western region of Saudi Arabia

Abstract: KEYWORDS ABSTRACTThe purpose of the current study is to determine the antioxidant activity of the most commonly used coffee brews in the Western region of Saudi Arabia. Further, total phenolic and flavonoid contents were measured and antioxidants properties including ferric reducing antioxidant power and ferrous ion chelating activity, DPPH radical scavenging activity, and scavenging of hydrogen peroxide assays were also determined. Results of study revealed that phenolic contents were 741, 835 and 578 µg/ml o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Flavonoids modulate a number of biological functions such as anti‐inflammatory and anti‐microbial activities with their ability to terminate free radicals, chelate metal ions, and scavenge free oxygen (Lin et al, 2016). Coffee may prevent cardiovascular diseases (CVD) and Parkinson’s disease, reduce the risk of developing type 2 diabetes and stroke, and prevent the formation of gallstones, Alzheimer’s disease, gallbladder diseases, and gout by reducing the level of uric acid in blood, (Al Doghaither et al, 2017; Ding et al, 2014; Lim et al, 2020). Liver diseases may be avoided by drinking two cups coffee in a day (Ergin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids modulate a number of biological functions such as anti‐inflammatory and anti‐microbial activities with their ability to terminate free radicals, chelate metal ions, and scavenge free oxygen (Lin et al, 2016). Coffee may prevent cardiovascular diseases (CVD) and Parkinson’s disease, reduce the risk of developing type 2 diabetes and stroke, and prevent the formation of gallstones, Alzheimer’s disease, gallbladder diseases, and gout by reducing the level of uric acid in blood, (Al Doghaither et al, 2017; Ding et al, 2014; Lim et al, 2020). Liver diseases may be avoided by drinking two cups coffee in a day (Ergin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Coffee may prevent cardiovascular diseases (CVD) and Parkinson's disease, reduce the risk of developing type 2 diabetes and stroke, and prevent the formation of gallstones, Alzheimer's disease, gallbladder diseases, and gout by reducing the level of uric acid in blood, (Al Doghaither et al, 2017;Ding et al, 2014;Lim et al, 2020). Liver diseases may be avoided by drinking two cups coffee in a day (Ergin et al, 2021).…”
mentioning
confidence: 99%
“…Most consumed coffee types in the western parts of Saudi Arabia [36] have been tested and it was found that the chelating potential of the tested Turkish coffee was much higher than that of the coffee types prepared with different methods The reducing power of an extract is associated with its ability to transfer electrons and is another proof of the presence of antioxidant activity [37]. The reducing power of the water extract of the coffee sample examined is very close to the test standard ascorbic acid.…”
Section: Discussionmentioning
confidence: 94%